Beach Erosion Variabiltiy during a Northeast Monsoon: The Kuala Setiu Coastline, Terengganu, Malaysia - Husain, Mohd Lokman; Yaakob, Rosnan; Saad, Shahbudin (Universiti Putra Malaysia Press, 1995)
It is widely accepted that beach erosion occuning along the coastline of the east coast states of Peninsular Malaysia is caused solely by the large waves of the northeast monsoon seasons. However, this study, which monitored 9 beach profile stations before and after a NE monsoon along a 25-km stretch of the Kuala Setiu coastline showed that only 2 of the 9 stations -located on both sides of the Setiu estuary river mouth - were eroded. The others showed accretion or negligible changes. Thus the assumption that the monsoon waves are the sole cause of beach erosion cannot be applied to all eroding coastlines. For some coastlines, theassumption may be only partly true. Wave refraction analyses show that, beside the large monsoon waves, the offshore bottom bathymetry and island shelters act as si~ specific factors either to help focus or disperse the energy of the monsoon waves to cause localized erosion or accretion. It is thus imperative that the modifYing effect of bottom topography and island shelters on monsoonal waves be considered if proper beach management policies and erosion mitigation measures are to be effective.